Placing Property A Legal Geography of Property Rights in Land - Byer, Amanda (Palgrave Socio-Legal Studies, 2023)
"This wonderfully readable and timely book takes readers on an intellectually compelling tour of land rights, customs, and practices across an impressive range of landscapes including pre-feudal Scandinavia, pre-Columbian America, the colonisation of the Caribbean and Ireland... Byer powerfully demonstrates the need to embed land laws within their geographical conditions and limits." -Nicole Graham, Professor and Associate Dean Education, Sydney Law School, The University of Sydney, Australia; author of Lawscape: Property, Law, Environment (Routledge, 2011) "This book uniquely brings together the usually disconnected domains of landscape, law, place, property and justice into a cohesive whole. This will become an invaluable source to readers seeking a comprehensive understanding of the contemporary scholarly questioning that is unsettling the once so seemingly settled absolute right of property." -Kenneth R. Olwig, Emeritus Professorof Landscape Architecture, Swedish University of Agricultural Science, Alnarp This open access book presents a legal geography of property rights in land through the lenses of landscape and critical spatial justice. It seeks to reassert the importance of landscape and place in property as an alternative to abstract concepts of property which dominate contemporary thinking. It investigates property's origins and uptake in the common law through the lenses of landscape and spatial justice, providing a genealogy of property, from its early origins in pre-feudal Scandinavia to its development as a cornerstone concept in English common law. It offers a new perspective and analytical tools to reconsider many accepted approaches to land in the law today. This book also contributes both to the decolonization of property law and critiques of property's unsustainability, as well as the examination of the role of law itself in facilitating large scale land changes that destroyplace, and the ramifications of this process. As such, it should be of interest to inter-disciplinary scholars working in the socio-legal, environmental and property law fields Amanda Byer is Post-doctoral Researcher at the Sutherland School of Law, University College Dublin, Ireland. .